2015
DOI: 10.1177/1540796915591988
|View full text |Cite
|
Sign up to set email alerts
|

Location Matters

Abstract: Despite decades of advocacy, most students with developmental disabilities continue to spend the majority of the school day in self-contained special education classrooms. However, there is tremendous variability of educational placement across the United States. Identification of geographic trends that explain this variability could provide opportunities for targeted advocacy. Using state-level data in Ohio, we tested the hypothesis that urbanicity predicts educational placement. Through mapping and multivari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(22 citation statements)
references
References 16 publications
3
19
0
Order By: Relevance
“…is not as evident (Brock & Schaefer, 2015;Kurth, Morningstar, & Kozeleski, 2014). We will review past research associated with LRE for students with extensive and pervasive support needs, and consider how access to general education leads to stronger, more inclusive schools.…”
Section: Needsmentioning
confidence: 98%
See 1 more Smart Citation
“…is not as evident (Brock & Schaefer, 2015;Kurth, Morningstar, & Kozeleski, 2014). We will review past research associated with LRE for students with extensive and pervasive support needs, and consider how access to general education leads to stronger, more inclusive schools.…”
Section: Needsmentioning
confidence: 98%
“…As would be expected, LRE variability is not only a concern among states, as within state variability among local education agencies (LEA) has also been identified. Brock and Schaefer (2015) uncovered wide variability among educational placement for students with significant disabilities in Ohio, and found that urban and urban-fringe districts were least likely to place students in general education 80% or more of the day. Cosier, White, Wang and Gao (2016) reported that in New York state, among 305 districts reporting LRE data for students with intellectual disability, almost 60% (180) reported that no students with intellectual disability were included in general education 80% or more of the day.…”
mentioning
confidence: 99%
“…This study is grounded in research in a number of areas related to placement of individuals with disabilities, including the variability in opportunities for access to general education curriculum and contexts (Brock & Schaefer, 2015), relationships between access to general education contexts and demographic and economic factors (Cosier & Causton-Theoharis, 2010), and the relationship between access to general education contexts and achievement (Cosier, Causton-Theoharis, & Theoharis, 2013). This particular study focuses on students with various disability labels, recognizing access to general education varies greatly by disability label, with stagnant growth in access to general education for students considered to have more ESNs, such as those with intellectual disability, autism, and multiple disability labels.…”
Section: Introductionmentioning
confidence: 99%
“…While analysis encompassed six disability eligibility categories (specific learning disability, other health impairment, autism, intellectual disability, multiple disabilities, and emotional behavioral disability), this study's focus was on disabilities encompassed in ESNs, including autism, intellectual disability, and multiple disabilities. Moreover, the study design is grounded in prior scholarship acknowledging factors associated with placement, such as geographic location (Brock & Schaefer, 2015;Kurth et al, 2014), race/ethnicity (e.g., Donovan & Cross, 2002;Fierros & Conroy, 2002; National Council on Disability, 2015), expenditure (Cosier & Causton-Theoharis, 2010), and income/socioeconomic status (O'Connor & Fernandez, 2006;Szumski & Karwowski, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…This Framework calls for all students to be educated in inclusive schools by 2015. That year has now receded into history and the wicked EQUITY-BASED INCLUSIVE SYSTEMS CHANGE 2 problem of inclusion remains unsolved as exemplified by its continued relative absence in schools worldwide (Brock & Schaefer, 2015;Kurth, Morningstar, & Kozleski, 2014;Smith, 2007).In this paper my aim is to propose a solution to the problem of inclusion, one that already has some acceptance within public education, but has yet to emerge as a coherent framework for professional practice. The reader has probably noted that I am putting quotes around some commonly accepted terms (i.e., "disability", "inclusion", "special").…”
mentioning
confidence: 99%